Occupy and the constitution of anarchy. Issue 2 (13th June 2019) - KINNA, RUTH; PRICHARD, ALEX; SWANN, THOMAS
Abstract: This article provides the first comparative reading of the minutes of the General Assemblies of three iconic Occupy camps: Wall Street, Oakland and London. It challenges detractors who have labelled the Occupy Wall Street movement a flash-in-the-pan protest, and participant-advocates who characterised the movement anti-constitutional. Developing new research into anarchist constitutional theory, we construct a typology of anarchist constitutionalising to argue that the camps prefigured a constitutional order for a post-sovereign anarchist politics. We show that the constitutional politics of three key Occupy Wall Street camps had four main aspects: (i) declarative principles, preambles and documents; (ii) complex institutionalisation; (iii) varied democratic decision-making procedures; and (iv) explicit and implicit rule-making processes, premised on unique foundational norms. Each of these four was designed primarily to challenge and constrain different forms of global and local power, but they also provide a template for anarchistic constitutional forms that can be mimicked and linked up, as opposed to scaled up.